AERODYNAMIC EVALUATION OF A MOTORCYCLE HELMET - Sanda BODEA; Iacob-Liviu SCURTU (Journal of Industrial Design and Engineering Graphics, 2022)
Traditionally, the product design has been based on physical experiments using different prototypes. Nowadays, the evolution of the computers has an important effect on the product design, it is based on the computer software from the conception phase. This paper presents an aerodynamic evaluation of a motorcycle helmet model using CFD simulation methods. The beginning of the evaluation includes the current state of the art regarding the computational methods for evaluate the aerodynamic performance of the motorcycle helmet, followed by the mathematical approach applied in this paper establishment of the airflow regime. Another part of the paper presents the CAD design of the motorcycle helmet modelled in five variants and performing the CFD simulation at 33.34 m/s airflow velocity for each helmet variant. The resulted aerodynamic force and the aerodynamic coefficient for each simulation model are discussed in the third part of the paper. The end of the paper presents the conclusions of this aerodynamic study, highlighting the advantages and disadvantages of using the CFD simulation to establish the helmet aerodynamics.